Legal Protection for Minority Shareholders in Bankruptcy (Case Study of Decision Number 1345 K/Pdt.Sus-Pailit/2024) - Nindita Salsabila Putri K; Satino Satino (Lambung Mangkurat Law Journal, 2025)
Investment is an important tool in the economy, but it carries risks such as abuse of authority and lack of transparency in corporate management. These risks are increasingly evident in the bankruptcy case of PT Sri Rejeki Isman Tbk (Sritex), which was declared bankrupt through Supreme Court Decision Number 1345 K/Pdt.Sus-Pailit/2024 due to heavy debt burdens and prolonged financial difficulties. This study aims to analyse the legal position of minority shareholders in bankruptcy and examine the available legal protection mechanisms. The method used is normative legal research with a legislative and jurisprudential approach. The results of the study show that the position of minority shareholders in bankruptcy is very weak, because they are not given formal space to play a direct role in the bankruptcy process and are placed as residual creditors with limited ability to fight for their interests. Normatively, legal protection for minority shareholders is regulated in the UUPT, but in practice, this mechanism is often ignored or becomes ineffective due to procedural obstacles. Therefore, it is necessary to strengthen legal mechanisms and regulatory reforms that provide formal participation for minority shareholders to submit objections to their losses so that their rights remain guaranteed in the bankruptcy process.